Development of representative volumetric element method for analysis of interlocking brick system - Shi, Tingwei (Curtin University, 2023)
This thesis examines the mechanical properties of interlocking bricks via experimental and numerical methods. It investigates compressive and shear properties (Part 1), effects of brick imperfections (Part 2), and develops a representative volumetric element method for analyzing interlocking brick systems (Part 3). Insights into the performance of interlocking brick structures, especially under varied loads and conditions, offer valuable guidelines for practical applications.